Cassava derivatives in the preparation of unconventional gluten-free snacks - Leonel, M. [UNESP]; Garcia, E. L. [UNESP]; Santos, T. P. R. [UNESP]; Fernandes, D. S. [UNESP]; Mischam, M. M. [UNESP] (Univ Putra Malaysia Press, 2019)
Products derived from cassava are not being sufficiently utilised by the food industry, despite their great potential in the preparation of gluten-free products. In the present work, mixtures of sour starch and leaf flour obtained from cassava were prepared and processed in a single screw extruder under different conditions of temperature, moisture, and screw speed, in order to obtain salty expanded snacks. The products were analysed in terms of expansion index, specific volume, hardness, colour, water-absorption index, water-solubility index, and sensory acceptance. Changes in the percentage of cassava leaf flour significantly affected the physical properties of the snacks, while they were less affected by moisture, temperature and screw speed. Processing with 6% cassava leaf flour blended with sour starch, in the presence of 16% moisture at an extrusion temperature of 100 degrees C and screw speed of 230 rpm produced highly crisp, light-coloured puffed snacks with good overall acceptability scores and the qualities that are desirable in expanded snacks. These results suggest that cassava sour starch and leaf flour can be used as ingredients in the production of extruded gluten-free products. (C) All Rights Reserved
Keywords: Manihot Esculenta; Leaf; Starch; Extrusion